2018
DOI: 10.1016/j.sjopt.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy combined with posterior-segment Ahmed valve implant: A case series study

Abstract: PC7 and PC8 Ahmed valve implantation via pars plana is a safe and useful option in patients with secondary refractory glaucoma who are either candidates for PPV or have been previously vitrectomized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We could not infer whether the BCDVA improvements in these eyes were due to postoperative IOP control or removal of the cataract. However, similar to de Frutos-Lezaun et al 's study [17], in our cohort, the overall BCDVA did not differ significantly from the preoperative value to the latest follow-up value. In contrast, Wallsh et al [18] and Jeong et al [21] reported postoperative improvements in BCVA.…”
Section: Faghihi Et Al (2007) [24]supporting
confidence: 90%
See 4 more Smart Citations
“…We could not infer whether the BCDVA improvements in these eyes were due to postoperative IOP control or removal of the cataract. However, similar to de Frutos-Lezaun et al 's study [17], in our cohort, the overall BCDVA did not differ significantly from the preoperative value to the latest follow-up value. In contrast, Wallsh et al [18] and Jeong et al [21] reported postoperative improvements in BCVA.…”
Section: Faghihi Et Al (2007) [24]supporting
confidence: 90%
“…To the best of our knowledge, this is the first study on AGV implantation for refractory glaucoma in the Caribbean region. Furthermore, the present study had the largest sample size with the longest follow-up among other studies on this topic [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations